2015
DOI: 10.1186/s12916-015-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of the effects of high intensity and low-to-moderate intensity exercise on physical fitness and fatigue in cancer survivors: results of the Resistance and Endurance exercise After ChemoTherapy (REACT) study

Abstract: BackgroundInternational evidence-based guidelines recommend physical exercise to form part of standard care for all cancer survivors. However, at present, the optimum exercise intensity is unclear. Therefore, we aimed to evaluate the effectiveness of a high intensity (HI) and low-to-moderate intensity (LMI) resistance and endurance exercise program compared with a wait list control (WLC) group on physical fitness and fatigue in a mixed group of cancer survivors who completed primary cancer treatment, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
173
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(190 citation statements)
references
References 40 publications
13
173
1
3
Order By: Relevance
“…In keeping with this view, in another RCT on patients with lung cancer, an adjunctive 12-week exercise intervention, consisting in moderate-intensity walking for 40 min per day, 3 days per week, was feasible and effective in reducing depressive symptoms and anxiety as assessed by the Hospital Anxiety and Depression Scale (HADS) 185 . Another RCT, examining the differential impact between a high-intensity and a low-moderate regimen of physical exercise in subjects with cancer, demonstrated that both regimens are effective in reducing measures of fatigue and physical functioning as compared to wait-list controls 186 . Moreover, physical exercise programs improved measures of work functioning.…”
Section: Physical Activitymentioning
confidence: 99%
“…In keeping with this view, in another RCT on patients with lung cancer, an adjunctive 12-week exercise intervention, consisting in moderate-intensity walking for 40 min per day, 3 days per week, was feasible and effective in reducing depressive symptoms and anxiety as assessed by the Hospital Anxiety and Depression Scale (HADS) 185 . Another RCT, examining the differential impact between a high-intensity and a low-moderate regimen of physical exercise in subjects with cancer, demonstrated that both regimens are effective in reducing measures of fatigue and physical functioning as compared to wait-list controls 186 . Moreover, physical exercise programs improved measures of work functioning.…”
Section: Physical Activitymentioning
confidence: 99%
“…This study used data collected in 2 randomized controlled exercise trialsdEXercise Intervention after Stem cell Transplantation study 15 and Resistance and Endurance exercise After Chemotherapy study 16,17 din cancer survivors, which were part of the Alpe d'HuZes Cancer Rehabilitation program. 18 The EXercise Intervention after Stem cell Transplantation study was a multicenter randomized controlled trial in which 109 patients, who were recently treated with autologous stem cell transplantation for multiple myeloma or (non-)Hodgkin lymphoma, were recruited from 9 hospitals.…”
Section: Patients and Measurementsmentioning
confidence: 99%
“…15 The Resistance and Endurance exercise After Chemotherapy study was a multicenter randomized controlled trial in which 277 patients diagnosed with breast, colon, ovarian, cervix, or testis cancer or lymphoma, who had recently completed primary cancer treatment (including chemotherapy), were recruited from 9 hospitals. 16,17 Approval for these studies was obtained from medical ethics committees of all participating centers, and all participants provided written informed consent.…”
Section: Patients and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Which type of exercise (e.g. aerobic, resistance), and at which intensity level, contributes most to the positive effect on CRF is not yet fully known4, 12, 13 and neither is the pathophysiological mechanism of this effect. Several studies have been performed investigating the effect of exercise interventions on CRF in patients with limited disease, and their results indicate improvement of CRF and increased muscle mass, but the effect sizes varied 14, 15, 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%